The effectiveness methanol extract clausena excavate on number of fibroblast and density of collagen fibers after tooth extraction - Efa Ismardianita; Widyawati Widyawati; Dewi Elianora; Wenny Rosalina; Lusi Nofrike; Vivi Y. Khairani (DiscoverSys Inc., 2019)
Objective: This study is made to identify the effect of extracts in Clausena excavata 50% on the number of fibroblasts and the density of collagen fiber in recovery after tooth extraction. Material and Methods: This is a true experimental designed with post-test only control group design, using 24 rats were divided into two groups, each group of three rats. Lower incisor tooth extraction performed lower left, into the tooth socket CMC applied to the control group and 0.5% extract treatment group Clausena excavata 50%. The number density of fibroblasts and collagen fibers were observed on days 3, 7, 14 and 21 with Haematoxylin Eosin staining and Mallory. The differences in density of collagen fibers observation group with Kruskal-Wallis test.Results: There are significant differences in a number of fibroblasts and density of collagen fibers between a control group and socket treatment group (p <0.05).Conclusion: The extract Clausena excavata 50% can fasten the wound recovery by increasing the number of fibroblasts and collagen fibers.